How Do Preoperative Antibiotics Affect Culture Yield in Diabetic Foot Infections?. (11th February 2017) - Young, Heather; Miller, Whitney; Burnham, Randy; Heard, Susan; Berg, Chrystal; Jenkins, Timothy C.
Abstract: The impact of preoperative antibiotics on culture of diabetic foot infection samples has not been studied. We found that increasing exposure to preoperative antibiotics was associated with less frequent growth of streptococci and anaerobes and more culture-negative results. In contrast, the yield of Staphylococcus aureus and Gram-negative bacilli was unaffected.